2016
DOI: 10.1264/jsme2.me16023
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequencing and Comparative Genomic Analysis of the Thermotolerant Acetic Acid Bacterium, <i>Acetobacter pasteurianus</i> SKU1108, Provide a New Insight into Thermotolerance

Abstract: Acetobacter pasteurianus SKU1108 is a typical thermotolerant acetic acid bacterium. In this study, the complete genome sequence of the SKU1108 strain was elucidated, and information on genomic modifications due to the thermal adaptation of SKU1108 was updated. In order to obtain a clearer understanding of the genetic background responsible for thermotolerance, the SKU1108 genome was compared with those of two closely related complete genome strains, thermotolerant A. pasteurianus 386B and mesophilic A. pasteur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The diluted samples (7 l) were dotted onto plates of YPGD medium and then incubated at 30, 37, and 39°C. pCM62 is a broad-host-range vector, and pCM83 is pCM62 harboring the nhaK2 gene of NBRC 3283. and 386B strains (15). Thus, xdhABC and paralogous genes may also be responsible for the thermotolerance in these strains.…”
mentioning
confidence: 96%
See 3 more Smart Citations
“…The diluted samples (7 l) were dotted onto plates of YPGD medium and then incubated at 30, 37, and 39°C. pCM62 is a broad-host-range vector, and pCM83 is pCM62 harboring the nhaK2 gene of NBRC 3283. and 386B strains (15). Thus, xdhABC and paralogous genes may also be responsible for the thermotolerance in these strains.…”
mentioning
confidence: 96%
“…The comparative genomics approach has the capability of identifying candidate genes responsible for the phenotypic difference present among closely related species. By using such approaches, we have identified some genes important for thermotolerance in AAB (14,15). In this study, we performed a comparative genomic analysis of 22 closely related A. pasteurianus strains to better understand the genetic background underpinning their phenotypes, and we found that there are some horizontal gene transfer (HGT) events and gene mutations that are responsible for the thermotolerant phenotype.…”
mentioning
confidence: 99%
See 2 more Smart Citations